Gen Z's Interest in Adventure Tourism Activities in Pine Forests - Risky Kusuma Hartono; D Dimyati (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
Tourism is one sector that has the potential to support economic activities. Indonesia has many interesting tourist destinations, both natural and man-made tourism, many villages that have developed into tourist villages, including Karyamukti Village with the superior tourist attraction Gunung Padang Site. Apart from the Padang Mountain Megalithic Site, the Karyamukti Tourism Village also has several tourist attractions, one of which is the pine forest area tourist attraction. The pine forest located in Karyamukti Village functions as a camping ground. The aim of this research is to determine the tourist interest of young people, especially Gen Z, towards tourism in pine forests, and also to find out what types of tourism activities are suitable to be implemented in pine forest tourism areas, especially adventure tourism activities. The research method used is a quantitative method, with the aim of finding out the percentage of Gen Z's interest in adventure tourism activities and the type of tourism activities desired. The research results show that the majority of Gen Z wants camping, glamping and outbound as adventure tourism activities in pine forests.